Epidural analgesia for intractable cancer pain - An old story used until now - SHoljakova, Marija; Kuzmanovska, Biljana; Durnev, Vesna; Andrijan Kartalov; Isjanovska, Rozalinda (ID Design 2012/DOOEL Skopje, 2020)
Intractable cancer pain is a chronic severe pain, affecting patient’s quality of life and presents aheavy health, social and family problem in many countries. Different methods for pain relief are proposed by the WHO. Epidural analgesia with opioids is one of the proposed methods. Aim of the study was to determine the effects of morphine, fentanyl and butorphanol used for epidural analgesia in intractable pain and to comment our experiences over a five-year-period, with regard to its actuality nowadays. Material and methods: Retrospective longitudinal observational study was carried at the University Clinic for Anesthesiology, Reanimation and Intensive Care in Skopje, Macedonia, between 2005-2010 and evaluated in 2017-2018. A total of 116 patients suffering from intractable pain were enrolled in the study. Exclusion criteria were: infective and metastatic processes in the spine, allergy to opioids, psychological problems and language barrier. After the pretreatment evaluation of the pain, patients were randomly assigned to receive three different opioids through epidural catheter placed from Th8-10 or L2-3. Results: There were no differences in pretreatment pain scores between the three groups (p>0.05). A significant onset of analgesia after 15 minutes was found for butorphanol, 20 minutes for fentanyl and 30 minutes for morphine group (p<0.05). The duration of the pain relief of butorphanol vs. fentanyl vs. morphine was 6h vs. 8h vs. 24 hours respectively.  Morphine had the longest duration of pain relief (p<0.05). Because of an increase in the pain threshold, the need of an increase of opioid doses was necessary. The most often patient’s reports of side effects were: itching, constipation, urine retention and bradypnea and there were no reports of nausea and vomiting. Conclusions: It was concluded that epidural analgesia with opioids is an effective and safe method for suppression of intractable pain.  In spite of the other alternatives in treatment of cancer pain, epidural analgesia with opioids still has an eminent place and its use is a challenge for professionals